On the use of length scale parameters to assess the static strength of notched 3D-printed PLA - Adnan A. Ahmed; Luca Susmel (Fracture and Structural Integrity)
This paper aims to investigate the accuracy of the Theory of Critical Distances (TCD) in estimating static strength of notched additively manufactured PLA as both notch sharpness and infill angle vary. The TCD takes as its starting point the assumption that the extent of damage under static loading can be assessed successfully by using two different material parameters, i.e. (i) a critical distance whose length is closely related to the material microstructural features and an inherent (i.e., a defect free) material strength. Plain and notched specimens of 3D-printed PLA were manufactured horizontally by making the deposition angle vary in the range 0?-90?. Using the TCD in the form of the Point Method, failures were predicted by directly post-processing the linear-elastic stress fields estimated through the well-known analytical solutions due to Glinka and Newport. Independently of the notch sharpness, the estimates being obtained were found to be highly accurate, falling within an error interval of about 20%. This result fully supports the idea that the TCD can successfully be used in situations of practical interest to design against static loading notched components of additively manufactured PLA by directly post-processing the results from simple linear-elastic Finite Element (FE) models.